Students’ Difficulties in Vocabulary Mastery - Machfudi, Moch. Imam; Afidah, Anissa’ul (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2022)
The purposes of this study were to describe the students’ difficulties in vocabulary mastery and the factors that caused students’ difficulties in mastering vocabulary. This research employed qualitative approach using phenomenology design. The data were gathered by observation, interview, and document review. Data technique and data source triangulation were used to validate the collated data. The result of this research revealed that several students had difficulties in vocabulary mastery. This study showed that: first, the difficulties encountered by students were that the students got difficulties in translating words or sentences in English into Indonesian and vice versa. Students also experienced difficulties in understanding the meaning of words, pronunciation, misspelling, and remembering or memorizing English vocabulary. Secondly, there were some factors that caused students got difficulties in vocabulary mastery. Students were reluctant to open dictionaries and less interested in learning English. This condition became the hindrance for them to practice English regularly. The other issues were external factors such as inadequate facilities and the negative influence of friends that at the end have made them difficult to learn English especially vocabulary mastery.